2005
DOI: 10.1523/jneurosci.3364-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

GABA Transporter Deficiency Causes Tremor, Ataxia, Nervousness, and Increased GABA-Induced Tonic Conductance in Cerebellum

Abstract: GABA transporter subtype 1 (GAT1) knock-out (KO) mice display normal reproduction and life span but have reduced body weight (female, Ϫ10%; male, Ϫ20%) and higher body temperature fluctuations in the 0.2-1.5/h frequency range. Mouse GAT1 (mGAT1) KO mice exhibit motor disorders, including gait abnormality, constant 25-32 Hz tremor, which is aggravated by flunitrazepam, reduced rotarod performance, and reduced locomotor activity in the home cage. Open-field tests show delayed exploratory activity, reduced rearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
170
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(192 citation statements)
references
References 58 publications
18
170
2
Order By: Relevance
“…An anxiety-prone behavior, which differed from our results with the open field and EPM tests, was observed in these mice (Jensen et al, 2003). These differences may be attributed to the different genetic background between the two mutant mice strains (C57BL/6J in the studies of Chiu et al (2005), whereas, mixed C57BL/6J and 129SvJ genetic background mice were used in our studies). However, the different strategy for making GAT1 knockout mice could contribute to the results of different phenotype.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…An anxiety-prone behavior, which differed from our results with the open field and EPM tests, was observed in these mice (Jensen et al, 2003). These differences may be attributed to the different genetic background between the two mutant mice strains (C57BL/6J in the studies of Chiu et al (2005), whereas, mixed C57BL/6J and 129SvJ genetic background mice were used in our studies). However, the different strategy for making GAT1 knockout mice could contribute to the results of different phenotype.…”
Section: Discussioncontrasting
confidence: 87%
“…Behavioral tests showed that GAT1-deficiency causes tremor, ataxia, and nervousness (Chiu et al, 2005). Nevertheless, there is little direct evidence to show the role of GAT1 in the pathogenesis of depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…329 Thus, the long-term antiepileptic action of tiagabine may be mediated by potentiation of the tonic inhibitory effect of GABA in the forebrain rather than enhancement of phasic inhibition. 330 Studies with a novel GABA-transporter inhibitor, EF1502, that potently inhibits GAT-1 and GAT-2 (BGT-1)-but not GAT-3 and GAT-4 -indicate that inhibition of GAT-2 potentiates the anticonvulsant activity of GAT-1. 331,332 GAT-3 can be selectively inhibited with SNAP-5114, which enhances GABA-mediated synaptic inhibition in the neocortex, indicating that GAT-3 plays a role in this brain region.…”
Section: Plasma Membrane Gaba Transportersmentioning
confidence: 99%
“…The loss of GAT1 function in mice results in significant neurological defects, including tremors, ataxia, and anxiety (Chiu et al, 2005). The reduced GABA uptake activity results in elevated extracellular GABA levels, which in turn result in an increased GABA A receptor-mediated tonic conductance in cerebellar granule and Purkinje cells (Chiu et al, 2005;also Jensen et al, 2003).…”
Section: Snf-11-deficient Phenotypesmentioning
confidence: 99%
“…The reduced GABA uptake activity results in elevated extracellular GABA levels, which in turn result in an increased GABA A receptor-mediated tonic conductance in cerebellar granule and Purkinje cells (Chiu et al, 2005;also Jensen et al, 2003). Jensen et al (2003) also report that GAT1-deficient mice lack a presynaptic GABA B -mediated conductance.…”
Section: Snf-11-deficient Phenotypesmentioning
confidence: 99%